FIXING CEMENT ROLE OF COMPLICATIONS OF FIXED DENTAL PROSTHESIS - D.V. Gryzodub (Ukrainian Medical Stomatological Academy, 2015)
Purpose: Study of influence on fixation cements on development intolerance to dental materials. Methods: The study involved 86 volunteers, who performed a special test. On discs of filter paper moistened with distilled water, mixed fixation cement was put. The disc was placed on the vestibular gum of the mouth on the upper or lower jaw. The application of the material lasted for 50 minutes. Then the ratio of the number of neutrophils was counted. Results: Most dental fixation cement cause the biological response of leukocyte cells in contact with the hard tissues of the tooth and to the oral mucosa. Moreover, there is a tendency in the difference of the reaction by groups of dental cements. Thus, in a group of zinc-polycarboxylate cements initial increase of neutrophils ranged from 105.8 to 111.3 %, in the group of glass ionomer cements from 92.6 to 96.9%, in the zinc phosphate cements group from 100.9 to 113 8%, and finally in the study group with zinc-oxide-eugenol cements within 106,5-117,2 %. Conclusions: The most common materials found a clear tendency to group differences, depending on the chemical components of the cement composition. During the provocative test with the study of the migration of neutrophils, it was determined that the least reactive group has biological properties of glass ionomer cements, the most provocative response showed zinc phosphate cements.